INTEGRATED MODEL OF INFLUENCER MARKETING STRATEGY AND SOCIAL MEDIA ACTIVITIES ON CONSUMER PURCHASE DECISIONS OF MSMES IN THE DIGITAL ERA: THE DUAL MEDIATING ROLES OF PERCEIVED VALUE AND CUSTOMER ENGAGEMENT - Fahdillah, Yosi; Sabrina, Hanan Laras; Suratno, Eddy; Pasae, Anjastanara; Ismayanti, Pupung (Jurnal Manajemen Terapan dan Keuangan, 2026)
Abstract This study examines the influence of influencer marketing strategy and social media activities on purchase decisions among Micro, Small, and Medium Enterprises (MSMEs) in the digital era, with perceived value and customer engagement as mediating variables. A quantitative approach was applied, and data were collected from 150 respondents through a structured questionnaire targeting active social media users who have purchased MSME products. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that influencer marketing strategy and social media activities have a positive and significant effect on perceived value, customer engagement, and purchase decisions. Furthermore, both perceived value and customer engagement significantly influence consumers’ purchase decisions. The findings also confirm that perceived value and customer engagement mediate the relationship between digital marketing strategies and purchasing behavior.This study highlights the importance of integrating influencer marketing and social media engagement to enhance consumer perceptions and involvement, which ultimately drive purchase decisions. The results provide both theoretical contributions to digital marketing literature and practical implications for MSMEs in developing effective and sustainable marketing strategies.  Keywords: Influencer Marketing Strategy, Social Media Activities, Purchase Decision, Perceived Value, Customer Engagement, MSMEs, Digital Era.